Gestión de registros médicos con blockchain - Caetano da Silva, Paulo (2025)
Internet applications and the use of other information technologies in the health sector are called e-Health, which aims to improve the flow of medical information through electronic means, optimizing the provision of services and the management of health systems. The challenges related to exchanging medical data between organizations revolve around the protection, confidentiality and privacy of patients’ sensitive and personal data (Lavina, 2018; Shi et al., 2020). Blockchain is an appropriate technology to mitigate these risks due to its characteristics of transparency, decentralization and immutability (Kim et al., 2022). Therefore, the goal of this work is to evaluate, through a systematic literature review (SLR), the use of blockchain to guarantee data privacy and security in e-Health systems. The methodology adopted is based on the recommendations of (Kitchenham & Charters, 2007) and the article quality criteria proposed by (Dybå & Dingsøyr, 2008). Searches were carried out in 5 scientific work repositories, which identified 3,214 articles related to the objective. After carrying out the methodological process, 19 articles resulted to be analyzed. The results achieved provide a state-of-the-art view of the use of blockchain in e-Health, indicating that the use of this technology is still incipient and little applied in the health data exchange environment. It is expected that the findings achieved can be beneficial for the healthcare domain to plan and develop a secure healthcare data management environment.